Our parliament : An introduction to the parliament of India - Kashyap, Subhash C. (New Delhi : National Book Trust, India, 2020)
A study of parliament in its proper historical perspective describing its multifarious activities, the working of the Rajya Sabha and the Lok Sabha, the role of presiding officers, the question hour, and other various procedural devices like different types of motions, the budgetary committee, and legislative processes, etc.
Keywords: India -- Parliament -- Politics and government